PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN ALIF ASGAR BARBERSHOP DI TANGERANG SELATAN - Alifh Ahmad Yasin; Joko Prasetiyo (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of service quality and price on customer satisfaction at Alif Asgar Barbershop in South Tangerang, both partially and simultaneously. The type of research in this writing is associative while the type of data in this study is quantitative. The population is 10, 623 with a sampling technique using the Slovin formula and the sample in this study was 100 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis test. The results of this study are that service quality has a significant effect on customer satisfaction with the hypothesis test obtained tcount> ttable or (10. 765> 1. 661) thus H0 is rejected and H1 is accepted, the regression equation Ŷ = 7. 544 + 0. 426 X1, the correlation value is 0. 722 where the value is in the interval 0. 60 to 0. 799 meaning that the two variables have a strong relationship level and a determination coefficient value of 52. 1%. Price has a significant effect on customer satisfaction with the hypothesis test obtained tcount> ttable or (8. 615> 1. 661), thus H0 is rejected and H2 is accepted. The regression equation Ŷ = 13. 054 + 0. 411 X2, the correlation value is 0. 656 where the value is in the interval of 0. 60 - 0. 799 meaning that the two variables have a strong relationship with a determination coefficient of 43. 1%. Service quality and price simultaneously have a significant effect on customer satisfaction with the hypothesis test obtained Fcount> Ftable or (80. 793> 3. 09), thus H0 is rejected and H3 is accepted. The regression equation Ŷ = 5. 513 + 0. 305X1 + 0. 231X2, the correlation value is 0. 785 where the value is in the interval of 0. 60 to 0. 799 meaning that the two variables have a strong relationship. The coefficient of determination is 61. 6% while the remaining 38. 4% is influenced by other variables.